2010
DOI: 10.1124/jpet.110.170159
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms in Organic Cation Transporter 1 (OCT1) in Chinese and Japanese Populations Exhibit Altered Function

Abstract: Organic cation transporter 1 (OCT1; SLC22A1) seems to play a role in the efficacy and disposition of the widely used antidiabetic drug metformin. Genetic variants in OCT1 have been identified largely in European populations. Metformin is increasingly being used in Asian populations where the incidence of type 2 diabetes (T2D) is on the rise. The goal of this study is to identify genetic variants of OCT1 in Chinese and Japanese populations, which may potentially modulate response to metformin. We used recent da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(103 citation statements)
references
References 22 publications
7
91
1
Order By: Relevance
“…The other allele frequencies were 0%. These were comparable to previously observed results (6,8,9,21,(27)(28)(29)(30)(31)(32)(33)(34). The observed frequencies were in Hardy-Weinberg equilibrium.…”
Section: Population Characteristicssupporting
confidence: 82%
See 4 more Smart Citations
“…The other allele frequencies were 0%. These were comparable to previously observed results (6,8,9,21,(27)(28)(29)(30)(31)(32)(33)(34). The observed frequencies were in Hardy-Weinberg equilibrium.…”
Section: Population Characteristicssupporting
confidence: 82%
“…Shu et al (43) previously demonstrated that OCT1-1022C>T variants are not related to decreased metformin uptake in HEK-293 cells and our in vivo study showed similar results. Chen et al (6) reported that the uptake of metformin in cells expressing OCT1-289C>A, -350C>T, and -616C>T was significantly reduced relative to the OCT1 wild types. However, in the current study, the genetic polymorphisms of OCT1-289C>T, -350C>T, -616C>T display no significant impact on the pharmacokinetics of metformin because there was no subject carrying the variant in the Korean population (Table I).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations